Fundamentos de projetos pedagógicos dos cursos de Arquitetura e Urbanismo : uma contribuição para o ensino - Gonçalves, Vanessa Vidal Magalhães (2019)
The present work approaches the discussions about the architect and urbanist formation, understanding the current scenario of the teaching and the architectonic production as a path based mainly on the mechanistic view. Believes that the formation of this professional should accompany the development of society, thus, the understanding of the systemic view raises the eye to broad and complex issues of contemporary cities. In this context, the relationships between the Brazilian architectural production, the professional performance, and what comprises the Pedagogical Projects of the Architecture and Urbanism Courses are discussed and analyzed. As a result, from the understanding of the mechanistic and systemic views and the philosophical and methodological principles of the Escola da Cidade / SP and the Faculty of Architecture and Urbanism of the University of Brasília – FAU-UnB are established Conceptual Guiding Axes and pedagogical principles that aim at the construction of a teaching of systemic architecture and urbanism. Thus, it is intended to contribute to the discussion on education and teaching, as well as to the conception of new pedagogical projects.